Identification of Phytochemical Compounds from Seaweed Extracts Eucheuma cottonii and Gracilaria verucossa and Their Effect on Bacteria Growth Escherichia coli - Januardi, Deki; Mulyadi, Aras; Yoswaty, Dessy (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
Seaweed is known to have several bioactive compounds that function as secondary metabolites and antioxidants. This study aims to determine the compounds in the seaweed Eucheuma cottoni and Gracilaria verucossa and their effects on Escherichia coli bacteria. This research was conducted from February to April 2022. The research method used was the experimental method by performing phytochemical tests and the disc method on bacteria. Conclusions can be drawn because of the results of the research that has been done. Seaweed E.cottoni and G.verucossa contain steroidal compounds. The effect on the growth of E.coli bacteria at concentrations (5%) 8.24 mm, (10%) 8.5 mm, and (15%) 8.62 mm was classified as moderate